Glutathione in women with blood-borne viral hepatitis B and C - O. A. Vanteeva; B. A. Fedorov (Acta Biomedica Scientifica, 2014)
The problem of viral hepatitis is of huge medical and social importance, but is still far from being resolved. The severity of course and prognosis of development of liver diseases are closely linked to the functional state of oxidant and antioxidant systems of an organism. Based on the research results we found that pregnant women with blood-borne viral hepatitis B and C had significantly higher level of oxidized glutathione and significantly lower level of reduced glutathione in comparison with indices of both healthy pregnant women and the women of control group.